Analysis of Animal Research Ethics Committee Membership at American Institutions - Alka Chandna; Lawrence A. Hansen; Justin R. Goodman (Animals, 2012)
Institutional Animal Care and Use Committees (IACUCs) were created to review, approve and oversee animal experiments and to balance the interests of researchers, animals, institutions and the general public. This study analyzed the overall membership of IACUCs at leading U.S. research institutions. We found that these committees and their leadership are comprised of a preponderance of animal researchers, as well as other members who are affiliated with each institution; some of whom also work in animal laboratories. This overwhelming presence of animal research and institutional interests may dilute input from the few IACUC members representing animal welfare and the general public, contribute to previously-documented committee bias in favor of approving animal experiments and reduce the overall objectivity and effectiveness of the oversight system.